Samoa : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper and Statistical Appendix reviews Samoa's record of economic reform, its economic performance to date, and future areas of reform focus. The paper highlights that reform of the taxation system has reduced Samoa's dependence on international trade taxes and enhanced the efficiency of the tax system. Tax reform was initiated in January 1994 with the introduction of a 10 percent value-added tax on goods and services. The paper also assesses the Samoan experience of reform implementation and remaining issues and challenges.